INVESTIGATING MALE AND FEMALE UNDERGRADUATE EFL STUDENTS’ ERRORS IN WRITING - Stardy, Rex (Journal of English Language and Culture, 2024)
Writing in English can be difficult for language learners, including for Indonesian learners. That is why they still make a lot of errors in their writings. There are many studies that have explored errors in students’ writings. However, not many directly compares between male and female students. This study tries to fill the gap by exploring the types of errors made by the male and female students. In total, there are 20 students whose work is used as the data for this research. There are 10 male and 10 female students. The writer analyzes a paragraph they wrote on the topic of “Children should not be given smartphones.” The students are from the second semester from the English Department at Bunda Mulia University. The errors are grouped into grammatical and mechanical errors with more specific subcategories for each. The findings of the research shows that the most frequent error is related to tense and structure, while the least is related to subject-verb agreement. This is for both male and female students. The writer also found that between the male and female students, they made very similar errors. Based on the result, the writer suggests that the teacher pays more attention to the mechanical errors that are frequently made by the students because this kind of error is easier to improve compared to grammatical errors. Students can also use programs like Grammarly to help improve their writing.